2021
DOI: 10.1177/09726527211022900
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Stage-wise Investment Preferences of Venture Capital and Private Equity Firms in India: An Empirical Exploration

Abstract: This article is a maiden attempt at exploring determinants of stage-specific investment choices of Indian venture capital and private equity (VCPE) firms. Analysis of 5,782 VCPE investment deals during 1998–2016 shows that firms’ preferences to invest in various stages (early vs. late) are significantly affected by the characteristics of the VCPE firms, features of the deal, and characteristics of the investee firms. More specifically, experience and ownership (foreign vs. domestic) of VCPE firm, type of deal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…This is a major finding since the majority of the IPOs in India have been witnessed by VCUs headquartered in the southern region of the country, as found in Table 6. While locational advantages of being situated in a particular region have been given importance in the literature (Florida and Smith, 1993;Chen et al, 2010;Dugar and Basant, 2021), the region is not found to have a statistically significant relationship in explaining the mode of exit. Further, we tested empirically the dummy variables for the other regions, i.e.…”
Section: Exit Options Of Venture Capitalistsmentioning
confidence: 98%
See 1 more Smart Citation
“…This is a major finding since the majority of the IPOs in India have been witnessed by VCUs headquartered in the southern region of the country, as found in Table 6. While locational advantages of being situated in a particular region have been given importance in the literature (Florida and Smith, 1993;Chen et al, 2010;Dugar and Basant, 2021), the region is not found to have a statistically significant relationship in explaining the mode of exit. Further, we tested empirically the dummy variables for the other regions, i.e.…”
Section: Exit Options Of Venture Capitalistsmentioning
confidence: 98%
“…To facilitate monitoring, VCs prefer to locate in regions with a concentration of profitable investments. This is because geography is an important factor in VC investment since VC investment requires frequent contact between VCs and the VCUs (Chen et al , 2010; Dugar and Basant, 2021). As IPOs and M&As are considered to be the successful modes of exit, it is worth knowing if region could influence the mode of exit in the VC industry.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Research suggests that entrepreneur actions are enabled and constrained by locality-related agent-structure interplay (Elkafrawi et al, 2022). More specifically, both location and industry of the investee firms are found to influence the stage of investment (Dugar & Basant, 2021). These factors are recognized in our empirical model and discussed in the following section.…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Nevertheless, repeated interaction with VC funds reduces not only the cash crunch but also leads to the establishment of sustainable business relationships. In addition, VC firms can build a reputation (Dugar & Basant, 2021) by sharing expertise and network linkages with the investee startups. There seems to be a trade-off between the quantity of money invested and the consistency of VC investment in startups.…”
Section: Conclusion and Implicationmentioning
confidence: 99%
“…Agency risk was mentioned in 18 of the 33 articles in the textual corpus; it is caused by divergences in interests between investors (principals) and entrepreneurs (agents) resulting from bad faith, conflicting objectives, or lack of capacity (Reid 1996;Bellavitis et al 2017;Cowden et al 2020;Dugar and Basant 2021). Differences between investors and entrepreneurs derive from information asymmetry, resulting in moral hazard and adverse selection (Parhankangas and Hellström 2007;Jarchow and Röhm 2020).…”
Section: Human Dimensionmentioning
confidence: 99%